Sensory properties and chemical composition of Sharri cheese from Kosovo - Agim Rysha; Frane Delaš (Mljekarstvo)
Food sensory properties, analyses and chemical composition are very important because they provide information about product quality and end-user acceptance or preferences. An assessment of sensory characteristics and chemical composition of mountain sheep and cow’s-milk cheese from shepherd’s huts and industrial manufacturers in Kosovo was carried out. Consumer-oriented tests using a 9 point hedonic scale were conducted in order to determine Sharri cheese acceptability. Chemical parameters (fat content, fat content of dry matter, acidity, protein, dry matter, mineral and water content and sodium chloride content) of 45-day brine cheese samples were also analyzed. Chemical and sensory assessment demonstrated large property differences. A recommendation stems from the results showing that the standardization of both artisanal and industrial production of Sharri cheese is required.